Adipokines and Visceral Adiposity Index in relation to clinical findings of NAFLD patients - Ebrahimi, Sara; Izadi, Azimeh; Pourghassem Gargari, Bahram; Aliasghari, Fereshteh (Progress in Nutrition, 2018)
Objective: The present study aimed to investigate the concentrations of some adipokines and their relationship with clinical findings of patients with nonalcoholic fatty liver disease (NAFLD). Additionally we measured the visceral adiposity index in relation to clinical characteristic of patients. Methods: This study was a cross-sectional study in 83 NAFLD patients. Plasma levels of omentin-1e-1, vaspin were measured. Anthropometric indices metabolic status was assessed. Visceral adiposity index and atherogenic index of plasma were calculated according to suggested formula. Results: Plasma omentin-1 levels directly correlated with weight of patients (p